THEORETICAL ASPECTS OF RESEARCH ON THE PSYCHOLOGICAL BASIS OF FORMING THE READINESS OF THE GROUND FORCES SERVICEMEN OF THE ARMED FORCES OF UKRAINE TO FULFILL COMBAT MISSIONS AS ASSIGNED - Filonenko, Lesia (Personality and environmental issues, 2025)
The current military and political situation in Ukraine, caused by the large-scale armed aggression of the Russian Federation, has necessitated a rethinking of the psychological training of the personnel of the Armed Forces of Ukraine. In this context, particular importance is attached to the formation of the psychological readiness of servicemen of the Ground Forces — the main combat component of the Armed Forces of Ukraine — for the effective execution of assigned combat missions in extremely complex, dynamic, and often dangerous combat conditions. A serviceman’s psychological readiness is not only the ability to maintain inner balance in stressful situations, but also an integral personal characteristic that encompasses motivational attitudes, volitional qualities, as well as cognitive and behavioral strategies. The successful development of such readiness ensures high combat efficiency, resilience to psychological stress, the ability to make rapid decisions, and adaptation to the changing circumstances of modern warfare. The scientific understanding of the psychological foundations of readiness is crucial not only for improving the system of combat training, but also for developing effective methods of psychological support for military personnel. The relevance of this topic is determined by the need to establish a comprehensive theoretical and methodological framework that will allow for an effective influence on the formation and development of combat readiness within the system of modern military education and training.